Sheep production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Sheep production in the tropics and sub-tropics / Gatenby. R.M. (1986). Longman, London. 352 pp. Price: 27.50 UKP.